Pematahan Dormansi Benih Kopi Arabika Kerinci dengan Berbagai Bahan Perendaman - Trias Novita; Evita Evita; Jasminarni Jasminarni (Universitas Batanghari Jambi, 2023)
Coffee seeds take a long time to germinate, as the tough seed coat can cause dormancy. This is because water absorption and gas exchange are disturbed and the seed coat is a mechanical barrier. Breaking of dormancy to maximize germination needs to be done before sowing the seeds. The aim of this study was to obtain an appropriate and effective soaking agent for breaking the dormancy of Kerinci arabica coffee seeds. The research was conducted using a Randomized Block Design (RBD), with various treatments for coffee seed immersion, namely: without immersion (p0), immersion with coconut water (p1), immersion in hot water (p2), and immersion with alang-alang root extract (p3). Parameters observed in the study were: maximum growth potential, germination and abnormal sprouts. The results of this study were (1) Proper and effective soaking materials were obtained for breaking the dormancy of Kerinci arabica coffee seeds, (2) Soaking Kerinci arabica coffee seeds with coconut water was more effective for maximum growth potential, germination and abnormal germination.